Biogas and Organic Manure Production from Anerobic Digestion of Rubber Plant Effluent, Gliricidia Leaves, and Inoculum: Energy Sustainability and Socio-Economic Development of Mauritania - Sidahmed Sidi Habib; Shuichi Torii; Kavitha Mol S.; Aravind Jayarajan (Clean Technologies)
This study analyzed the anaerobic co-digestion of inoculum (I), rubber plant effluent (RPE) and Gliricidia leaves slurry (GLS) at different mixing ratios for the simultaneous production of methane and organic fertilizer. The results were analyzed for volatile fatty acids, pH, C/N ratio, and methane production. The organic quality of the substrate mixture before and after anaerobic digestion was analyzed for total organic carbon, total nitrogen, potassium, and phosphorus contents. This study concluded that the inoculum, rubber plant effluent (RPE), and Gliricidia leaves slurry (GLS) mixed at the ratio of 10:2:2 showed higher methane production than other experiments conducted at different mixing ratios. The nitrogen, potassium, and phosphorus contents of the substrates were increased after anaerobic digestion. However, the organic carbon content in the substrate decreased in all experiments. This research recommends the planting of rubber trees and Gliricidia maculata to promote energy sustainability and the socio-economic development of Mauritania.